The adolescent and his experience during the intermediate stage - Sophía González Zúñiga; Ana María Quezada Ugalde (Universidad de Costa Rica, 2015)
Introduction. Adolescence is considered a vulnerable stage on all people's life. Within the health system, this population is characterized by a low coverage exclusively aimed at finding the problems, which requires more specialization. This article aims to present the situational diagnosis of a group of teenagers in the intermediate stage in order to further develop a program of Pediatric Nursing care for the adolescent in the intermediate stage, in an institution of secondary education for the years 2013-2014. Method. The implemented methodology is qualitative with a constructivist epistemological approach; triangulating the information gathered performed data analysis. Results. Among the main findings of the diagnostic phase was obtained teenagers prioritized issues such as the phenomenon of drugs and situations related to sexuality; also describe their experience along this stage of life, the changes that occurred, and interaction with peers and family, information necessary for a pediatric nurse practitioner intervene appropriately. The main findings on the diagnose phase show that adolescents prioritized issues like drugs and situations related to sexuality. They also describe their experience through this life stage, all the changes occurred and the interaction with partners and family. Conclusion. The study reveals that it is essential to establish a first contact with the adolescent to identify all their needs in an integral form, and to give them the opportunity to propose possible solutions. Being continuously in contact stimulates the development of empathy in order to obtain a greater openness from the individual to the nurse-practitioner as an accompaniment figure throughout their adolescence.